Konvergensi Setengah Hati : Invasi Konten Media Sosial dalam Program Berita Televisi di TVOne - Vivin Lizetha; Angga Prawadika (Jurnal Media dan Komunikasi, 2021)
Growth of technology give big impact to development and changes in mass media. Today, even though broadcast media like radio and television still have place in the heart of audience, however should be recognized that the existence of social media, it must be recognized that the existence of social media has a significant impact on media development. Mainstream media, especially television broadcast media, are starting to look for ways not to be abandoned by their audience. They began put in social media content into television programs. That happened on all shows in television programs. No exception in the news program on TVOne. Therefore, it is interesting to study how the transfer of social media content to television news programs is a way for TVOne to survive in the midst of the onslaught of social media. This research focuses on news programs on TVOne that take social media content into the show. We will use descriptive qualitative research using the case study method and use the political economy theory of the media.